2006
DOI: 10.1007/s00406-006-0698-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke affective or apathetic depression and lesion location: left frontal lobe and bilateral basal ganglia

Abstract: This study was designed to examine the correlation between damage to the basal ganglia or frontal lobe and depression status (both affective and apathetic dimensions) in 243 stroke patients. We assessed the affective dimension in post-stroke depression (PSD) using the Zung Self-rating Depression Scale (SDS) and the apathetic dimension in PSD using the apathy scale (AS). We classified basal ganglia or frontal lobe damage into four groups: no damage, damage to the left side only, damage to the right side only, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 14 publications
11
88
1
3
Order By: Relevance
“…This finding was in accord with previous studies (Armstrong et al, 2017; Lim et al, 2017). However, there was no significant association between PSD and other clinical characteristics, such as lesion location (Guiraud, et al, 2016; Hama et al, 2007; Metoki et al, 2016), although among some of previous studies the results about lesion location remained controversial.…”
Section: Discussionmentioning
confidence: 97%
“…This finding was in accord with previous studies (Armstrong et al, 2017; Lim et al, 2017). However, there was no significant association between PSD and other clinical characteristics, such as lesion location (Guiraud, et al, 2016; Hama et al, 2007; Metoki et al, 2016), although among some of previous studies the results about lesion location remained controversial.…”
Section: Discussionmentioning
confidence: 97%
“…Major PSD has been frequently associated to left frontal lesions [37,45,46]; furthermore, a modification of such anatomical substrate during the poststroke period has been proposed [40]. Data from Hama et al [20] have suggested differential anatomical substrates of two different subtypes of PSD: "apathetic" PSD, associated to bilateral basal ganglia damage, and "affective" PSD, associated to left frontal lobe lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Results from previous studies investigating the anatomical substrate of post-stroke apathy are quite inconsistent. It has been related to right side of lesion [8]; furthermore, it has been related to bilateral subcortical damage [20] and to reduced concentration of N-acetyl-aspartate in left frontal lobe [18], independently from the site of lesion. Finally, a functional study has reported a relationship between apathy and hypoperfusion of both frontal lobes after stroke [29].…”
Section: Psychiatric Historymentioning
confidence: 99%
“…[11][12][13][18][19][20] Patients completed the AS within 1 month after admission. The AS consists of 14 questions concerning spontaneity, initiation, emotionality, activity level, and interest in hobbies.…”
Section: Apathy Scalementioning
confidence: 99%
“…[11][12][13]17 Patients completed the SDS within 1 month after admission. We classified the patients into two groups according to their score: a non-depressed group (SDS score <45 points) and a depressed group (SDS score Ն45 points).…”
Section: Self-rating Depression Scalementioning
confidence: 99%